Jamaica Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
This Report on Observance and Codes-Accounting and Auditing (ROSC-A&A) assesses the corporate sector accounting, financial reporting, and auditing practices in Jamaica. It builds on its predecessor, a 2003 ROSC-A&A, and its aims to assist the Government of Jamaica's efforts to strengthen accounting and auditing practices and to enhance financial transparency in the corporate sector, so as to support the Government's economic reform program and provide greater confidence to current and potential investors with respect to the financial reporting environment. Jamaica has embarked on an economic reform program whose main objectives are to contain the country's growing economic and external vulnerabilities and address economic imbalances, while putting the country on a path to sustainable growth. Important reforms include: (a) strengthening public finances, including through comprehensive tax reform, expenditure rationalization, and improved public debt management and public financial management; (b) enhancing the resilience of the financial sector through strengthened supervisory, regulatory, and crisis-management frameworks; and (c) improving growth generating efficiency through enhancements to the business environment and strengthened institutional capacity and governance.